2010
DOI: 10.1590/s0102-695x2010000100023
|View full text |Cite
|
Sign up to set email alerts
|

Clerodendron glandulosum Coleb., Verbenaceae, ameliorates high fat diet-induced alteration in lipid and cholesterol metabolism in rats

Abstract: RESUMO: "Clerodendron glandulosum Coleb., Verbenaceae, melhora a dieta rica em gordura induzida por alteração no metabolismo de lipídios e colesterol em ratos." Este estudo foi realizado para avaliar a eficácia do extrato liofilizado das folhas de Clerodendron glandulosum Coleb., Verbenaceae (FECG), em alterar o metabolismo de lipídios e colesterol em ratos hiperlipidêmicos alimentados em uma dieta rica em gordura. Plasma e perfil lipídico hepático, lipídeos e enzimas que metabolizam o colesterol em tecidos-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
5
13
0
Order By: Relevance
“…These results are in tune with a previous study from our laboratory reporting reduced absorption of lipids through intestine and excretion of the same through faeces in CG treated hyperlipidemic rats (Jadeja et al, 2010b). In addition, HFD fed OB mice recorded significant increment in size and mass of abdominal, renal and epididymal fat pads while, this increment was prevented in CG supplemented OB mice.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in tune with a previous study from our laboratory reporting reduced absorption of lipids through intestine and excretion of the same through faeces in CG treated hyperlipidemic rats (Jadeja et al, 2010b). In addition, HFD fed OB mice recorded significant increment in size and mass of abdominal, renal and epididymal fat pads while, this increment was prevented in CG supplemented OB mice.…”
Section: Discussionsupporting
confidence: 91%
“…Traditionally, cross sections of people across Manipur consume decoction of CG leaves for treating diabetes, obesity and hypertension (Jadeja et al, 2009). Recent studies from our laboratory have shown that, CG aqueous extract can improve fructose induced insulin resistance and hypertension (Jadeja et al, 2010a), regulate high fat diet induced hyperlipidemia in rats (Jadeja et al, 2010b) and prevent HFD induced hepatic steatosis (Jadeja et al, 2010c). In addition, safety evaluation of CG aqueous extract in Swiss albino mice has revealed its LD 50 indices to be higher than 3000 mg/kg (Jadeja et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, ARCE‐treated rats fed the ATH diet recorded a significant decrement in the tissue lipid load in cardiac and hepatic tissue and a higher elimination of TC and TG through faeces. Previous studies have reported that herbal extracts are capable of increasing elimination of dietary TC and TG through faeces primarily by inhibiting its intestinal absorption 17. Hence, it can be presumed that hypolipidaemic and hypocholesterolaemic properties of ARCE are possibly due to its ability to hamper absorption of TC and TG in the intestine and this possibility needs further scrutiny.…”
Section: Discussionmentioning
confidence: 97%
“…A good example of this is Clerodendron glandulosum Coleb. This herb, found in north eastern states of India [1], is a folklore medicine consumed by urban and tribal populace of Manipur against obesity, diabetes, and hypertension [2, 3]. Recently, it has been reported that aqueous extracts from Clerodendron glandulosum Coleb.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that aqueous extracts from Clerodendron glandulosum Coleb. can regulate high-fat-diet induced hyperlipidemia in rats [3], improve fructose induced insulin resistance and hypertension [4], and prevent high-fat-diet-induced hepatic steatosis [5]. …”
Section: Introductionmentioning
confidence: 99%